HUBUNGAN KOMPETENSI DAN DISIPLINAN KERJA DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA - Tahrir Tahrir (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Background this research from fenomena at Psychologycal Faculty of  UIN Sunan Gunung Djati Bandung, that student motivation to learn is very low, for example: student present is small then 75%. Beside, 65% educational background lectures was not from pure psychology. According to student opinion there are much lectures from Psychology Faculty do not competence in their job matter. Research design is suvey and research method is causality because the research goal is know how streng effect one variable to an other variable. Total sampling are 100 students. Hypotetis test with Product Momant from Pearson because scale of data is interval. The result is Lecture Competence have possitive correlation and significant with Student Motivation to Learn with rxy value: 0.629, rtable 0.195, and p=0.000 (p<0.05). So Lecture Dicipline to Work have possitive correlation and significant with Student Motivation to Learn with rxy value: 0.755, rtable 0.195, and p=0.000 (p<0.05). So Lecture Competence and Dicipline to Work have possitive correlation and significant with Student Motivation to Learn with rxy value:0.762, rtable : 0.195, and p=0.000 (p<0.05), and  is 58%